Penerapan Restful API Pada Push Notofication Untuk Rekam Data Perwalian - Arif Harbani; Pangestu Septiansyah (Universitas Binaniaga Indonesia, 2023)
Guardianship is counseling carried out by students with guardian lecturers, to provide direction for the tutoring process at the tertiary level. Currently the academic guardianship system has an indication of a problem, which is when the student has a guardianship record every semester. And in the existing guardianship academic system, they don't have that yet. Because it is caused by students who are on leave and students who are repeating courses. In addition, guardian lecturers cannot track courses taken by students, this can be said to be ineffective. Thus, data recording and Reminder Information were developed, so that guardian lecturers can carry out the teaching and learning process more effectively and students can carry out lectures properly, because of the technology used in the academic system. This research uses the RestFul API method on Push Notifications to Record Guardianship Data to be more effective. Then to Respond and Request trust history data, namely using JSON, so that it is more structured and easier to use. The methods applied are Get, Post, Put, and Delete. Each method has uses, namely displaying trusteeship data records using the Get method, then providing guardianship records using the Post method, as well as changing records using the Put method and deleting using the Delete method. With the implementation of the RestFul API in Push Notification for the trust data recording system, a feasibility test has been carried out and obtained a value of 81.05%, which means that the application built is very feasible so that it can help the process of recording trust data.